2005
DOI: 10.1177/1090198105276211
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial Testing a Worksite Sun Protection Program in an Outdoor Recreation Industry

Abstract: Health communication campaigns intended to reduce chronic and severe exposure to ultraviolet radiation in sunlight and prevent skin cancer are a national priority. Outdoor workers represent an unaddressed, high-risk population. Go Sun Smart (GSS), a worksite sun safety program largely based on the diffusion-of-innovations theory, was evaluated in a pair-matched, group-randomized, pretest-posttest controlled design enrolling employees at 26 ski areas in Western North America. Employees at the intervention ski a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
168
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(171 citation statements)
references
References 42 publications
3
168
0
Order By: Relevance
“…[13][14][15][16] This belief arose because outdoor workers are exposed to UV every day, unlike indoor workers, so that their skin acclimates by thickening the stratum corneum and by producing the pigment melanin (tan). However, contrary to this popular belief, outdoor workers can get numerous sunburns and can also experience blistering events [28][29][30][31] reviewed by Glanz. 32 For example, the study by Buller et al 30 found 45% of the ski area employees got sunburned and 8% received blistering sunburns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16] This belief arose because outdoor workers are exposed to UV every day, unlike indoor workers, so that their skin acclimates by thickening the stratum corneum and by producing the pigment melanin (tan). However, contrary to this popular belief, outdoor workers can get numerous sunburns and can also experience blistering events [28][29][30][31] reviewed by Glanz. 32 For example, the study by Buller et al 30 found 45% of the ski area employees got sunburned and 8% received blistering sunburns.…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to this popular belief, outdoor workers can get numerous sunburns and can also experience blistering events [28][29][30][31] reviewed by Glanz. 32 For example, the study by Buller et al 30 found 45% of the ski area employees got sunburned and 8% received blistering sunburns. Another study measured alpine skiers who got 0.5-7.6 times the minimum erythemal dose (MED), or the minimum amount of UV dose needed to produce a mild sunburn, for white individuals with skin type II and 10% got more than 1 MED/h during peak exposure times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All ski areas were National Ski Area Association (NSAA) members and had at least two aerial chairlifts. 22 See Buller et al 22 for ski-area recruitment procedures.…”
Section: Participantsmentioning
confidence: 99%
“…25 Size and location (a surrogate for climate) of ski areas were the primary matching variables; ownership structure and the proportion of female employees were also included in the matching. 22 Trained staff interviewed guests on chairlifts with a minimum run time of 4 minutes during 3-day periods (1 weekend day and 2 weekdays) to obtain pre-intervention data from January to April 2001 and post-intervention data from January to March 2002. Pairs of ski areas were visited during the same week in both years.…”
Section: Experimental Design and Survey Proceduresmentioning
confidence: 99%